2022
DOI: 10.3389/fresc.2022.920496
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Co-production Within a Mental Health Recovery College Dementia Course: Perspectives of A Person With Dementia, Their Family Supporter and Mental Health Staff

Abstract: BackgroundUndertaking co-production as a power-sharing way to improve mental health dementia services remains uncommon, suggesting opportunities to apply knowledge from lived experience of people with dementia, may often be missed. One barrier is stigma, assuming people with progressive cognitive impairment cannot manage this level of participation, support peers nor offer a “valid” perspective.PurposeThis paper shares knowledge gained from a service evaluation that explored various experiences of a person wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The co-production of the courses with people with dementia was viewed as a strength. These findings resonate with a recent qualitative case study exploring the experiences of people with dementia who undertook a Recovery College dementia course, where co-production and peer-to-peer learning emerged as important aspects of the support received (West et al , 2022). Co-production activities promoted “breaking down the ‘them and us’ barriers common in traditional health-care professional-service user relationships”.…”
Section: Discussionsupporting
confidence: 80%
“…The co-production of the courses with people with dementia was viewed as a strength. These findings resonate with a recent qualitative case study exploring the experiences of people with dementia who undertook a Recovery College dementia course, where co-production and peer-to-peer learning emerged as important aspects of the support received (West et al , 2022). Co-production activities promoted “breaking down the ‘them and us’ barriers common in traditional health-care professional-service user relationships”.…”
Section: Discussionsupporting
confidence: 80%
“…A Canadian initiative is currently co‐producing a user‐led framework for evaluating RCs 26 . Increasingly, RC research is diversifying, exploring the experiences of students with specific diagnoses and studying the impacts of specific RC courses 21,27,28 . One of the first pieces of RC research to have explored the effects of the Covid‐19 pandemic and the move online is that of Rapisarda et al 29 Their study found online RCs to be particularly effective at combatting anxiety, and advocates RCs as a cost‐effective and accessible public mental health response to crisis situations 29 …”
Section: Introductionmentioning
confidence: 99%
“…Existing clinical relationships between mental health staff co-producing Recovery College dementia courses and people living with dementia were used to recruit co-producers with lived experience (Cheffey et al., 2013 ; West et al., 2022 ). Staff approached people they considered would benefit from work that moved beyond the current therapeutic relationship to one where the person actively applies their skills, experience, and knowledge to co-producing a course (CMOC5).…”
Section: Resultsmentioning
confidence: 99%